(untitled) (Advances in Military Technology, 2022)
The deflection from classical Chemical Warfare Agents in military use has been currently noticed. That is why questions’ solution concerning contamination after their use importantly decreases. On the other hand, a possibility of contamination development after both military and terroristic Toxic Industrial Chemicals usage is very high. Despite these very important facts, necessity of solutions of questions concerning study of suits’ protective properties used for specialists’ isolative protection increases. In this way, the gained results principally affect the evaluation of effectivity of accepted protective measurements in all kinds of military operations conducted by both Czech Armed Forces Chemical Corps specialists and specialists from Fire Rescue Brigades. The main aim of the article is to point to some properties of butyl-rubber polymer mixture coated on polyamide fabric considering selected liquid aliphatic saturated hydrocarbons in a homological line with the use of the PIEZOTEST method which uses a QCM detector.